2005
DOI: 10.1039/b511005j
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme responsive polymer hydrogel beads

Abstract: We report on a new class of enzyme responsive polymer hydrogels, the molecular accessibility of which can be changed selectively by enzymes present in a sample fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 24 publications
3
71
0
Order By: Relevance
“…Similarly, proteolytically degradable PEG hydrogel networks can also be used to incorporate and release growth factor proteins [49]. It has been recently demonstrated that a series of enzyme-cleavable linker-containing hydrogel beads can specifically respond to target enzymes for the controlled release of growth factors [166]. Hydrogel formation can also be triggered by enzyme-catalysed reactions.…”
Section: Growth Factor Release On Demandmentioning
confidence: 99%
“…Similarly, proteolytically degradable PEG hydrogel networks can also be used to incorporate and release growth factor proteins [49]. It has been recently demonstrated that a series of enzyme-cleavable linker-containing hydrogel beads can specifically respond to target enzymes for the controlled release of growth factors [166]. Hydrogel formation can also be triggered by enzyme-catalysed reactions.…”
Section: Growth Factor Release On Demandmentioning
confidence: 99%
“…[62][63][64][65][66][67][68][69][70][71] However, the structural changes of protein-responsive hydrogels in the literature were based on the degradation of polymer networks caused by an enzymatic reaction. Studies on protein-responsive hydrogels that undergo reversible swelling/shrinking in response to a target protein have not been undertaken in spite of their potential applications as smart biomaterials.…”
Section: Antigen-responsive Hydrogelsmentioning
confidence: 99%
“…Thus, the enzyme-responsive hydrogels are typically made out of enzyme-sensitive substrates and another joint component able to direct or control specific interactions leading to macroscopic transitions. The enzyme catalytic action on the substrate leads to the swelling or collapse of the respective gels and/or the transformation of its surface properties [2,33,34]. This enzyme responsive class includes enzyme-degradable hydrogels: albumine and chitosan hydrogels N-acetyl-Dglucosamine, among others.…”
Section: Enzyme Responsive Polymersmentioning
confidence: 99%
“…[2,33,34] Enzyme catalytic action on the substrate lead to gels swelling/collapse, or the transformation of surface properties Proteases-responsive hydrogels: typically the preformed network is exposed to a protease enzyme, and hydrolysis of protein or peptide based crosslinkers in the network leads to gel degradation and subsequent release of encapsulated contents. …”
Section: Enzyme-responsivementioning
confidence: 99%
See 1 more Smart Citation